2021
DOI: 10.1111/jdi.13620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression on progression to end‐stage renal disease or pre‐end‐stage renal disease death in advanced diabetic nephropathy: A prospective cohort study of the Diabetes Study from the Center of Tokyo Women’s Medical University

Abstract: Aims/Introduction: This study aimed to determine the effect of depression on the progression to end-stage renal disease (ESRD) and pre-ESRD death in patients with advanced diabetic nephropathy. Materials and Methods: This single-center prospective cohort study enrolled Japanese patients with type 2 diabetes and advanced diabetic nephropathy. The total Patient Health Questionnaire-9 score was used to evaluate depression at baseline and classified patients into: no, mild and severe depression groups. The outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Among them, 15 were excluded due to the following reasons: 7 lacked sufficient data to generate reliable risk estimates, and 8 described the relationship between depression and diabetes/diabetes complications ( Fig 1 ). Ultimately, 30 studies were investigated, where 24 were about DN predicting depression [ 18 41 ] and 6 were about depression predicting DN [ 42 47 ] (Tables 1 and 2 ). It was noted that 4 of the final 30 studies reported HR and one reported RR in risk evaluation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 15 were excluded due to the following reasons: 7 lacked sufficient data to generate reliable risk estimates, and 8 described the relationship between depression and diabetes/diabetes complications ( Fig 1 ). Ultimately, 30 studies were investigated, where 24 were about DN predicting depression [ 18 41 ] and 6 were about depression predicting DN [ 42 47 ] (Tables 1 and 2 ). It was noted that 4 of the final 30 studies reported HR and one reported RR in risk evaluation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were from Europe [ 21 , 23 , 28 , 37 , 40 , 46 ], one from Africa [ 29 ], 16 from Asia [ 19 , 20 , 22 , 24 , 26 , 30 33 , 35 , 36 , 38 , 39 , 41 , 45 , 47 ], and 7 from America [ 18 , 25 , 27 , 34 , 42 44 ]. There were 10 prospective cohort studies [ 18 , 22 , 25 , 35 , 37 , 40 , 43 , 44 , 46 , 47 ], 18 cross-sectional studies [ 19 21 , 23 , 26 30 , 32 , 33 , 35 , 36 , 38 , 39 , 41 ], 2 case-control studies [ 23 , 31 ]. The largest number of participants were 933,211, while the longest follow-up time was 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…The Theory of Sugar and Collateral Miscellaneous Diseases points out the pattern of uncertain complications of diabetes: the regular characteristics, guiding ideology, and theoretical basis of “the disease enters the collaterals for a long time, from collaterals to miscellaneous collaterals.” And Ye Tianshi's concluded that “long illness enters collaterals.” Based on the ancient and modern theory, the operation or permission for predicting the occurrence of different complications in different periods of time is explored from the methodology of five stages: occult period, early stage, middle stage, and late stage. TCM syndrome differentiation of DN is the name of pseudodiabetic kidney disease in TCM, focusing on the essence of pathological changes and the relationship between evil and good at a specific stage of diabetes, to understand the etiology, disease location, disease situation, pathogenesis, and nature, in order to achieve the purpose of syndrome differentiation from the new balance theory [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher PHQ‐9 scores were associated with increased odds ratios for retinopathy, neuropathy, and end‐stage renal disease in both type 1 diabetes and type 2 diabetes 9 , 14 . Furthermore, a longitudinal study showed an association between depression and diabetic retinopathy 27 and nephropathy 19 , 28 . Therefore, it is important to consider strategies to reduce depressive symptoms to prevent the onset and progression of type 1 diabetes‐related complications.…”
Section: Discussionmentioning
confidence: 99%